Syariah Sebagai Hasil Pemikiran: Produk Ijtihad Konvensional dan Ijtihad Kontemporer - Albia, Rahma (IAI Darussalam, 2024)
It cannot be denied that the contribution of Islam (Syariah) and Muslim thought is very large to the continuity and development of legal thought. The purpose of this paper is to find out how the origin of sharia exists, then what are the results of conventional ijtihad products and contemporary ijtihad and which reasons are more obligatory to obey between Fikih and Codification. The research uses a qualitative method. While the approach used in this research is a normative-historical approach. The findings produced in this study are that in Indonesia, one of the legal systems in force is Islamic law. In the Islamic legal system, there are types of Islamic legal thought products in Indonesia, which include: fiqh thought products, fatwas, tafsir, court decisions (Jurisprudence), and legal thought products (codification) and the results of the Supreme Court plenary meeting, should be enforced and enforced honestly and fairly. Then the products of Islamic legal thought that have been institutionalized and obeyed by the Indonesian people are Fiqh, Tafsir, Fatwa, Jurisprudence and Legislation. The process of the birth of these four things cannot be separated from the development of the dynamics of community life from time to time in collaboration with Indonesian conditions.